DE-IDOLIZING WALI IN THE TARIQAT TRADITION (THE STUDY OF THE SAINTHOOD CONCEPT OF HADRATUS SHEIKH HASYIM ASY’ARI AND HIS INFLUENCE IN INDONESIA) - Ni’am, Syamsun; Zuhriyah, Lailatuzz; Nurhayati, Dwi Astuti Wahyu; Marpuah, Siti (Jurnal ’Ulwan, 2025)
This article examines the views and conceptions about the Sufism concept –precisely the sainthood concept in the tariqat tradition of Hadratus Sheikh Hasyim Asy’ari. According to Alwi Shihab, Sheikh Hasyim was devoted; Sheikh Hasyim is one of the leading Sunni sufi of Nusantara aligned with Sunni Sufis of Nusantara, such as Sheikh Nurudin al-Raniri and ’Abd al-Samad al-Palimbani. Sheikh Hasyim is also known as the founding father of the largest Islamic organization in Indonesia, Nahdaltul Ulama (NU). As a charismatic cleric in Nusantara, especially in NU, his views and thoughts greatly influenced Nusantara’s community constellation and religiosity. Among his views that have had major implications until now is a sainthood concept (al-walayah) in the tariqat tradition. In this context, Sheikh Hasyim was very critical of labelling someone on sainthood, especially a tariqat teacher (Murshid) because this would make someone idolize blindly, which can lead to polytheistic behaviour toward Allah. Even more interesting is his view and conception of sainthood, “de-idolizing sainthood in the tariqat tradition”. This is not much followed, even though it tends to be ignored by his followers, particularly by the tariqat grouped in Jam’iyyat Ahl al-Thariqah al-Mu’tabarah al-Nahdliyah belonged to NU. This is the reason why researchers are studying this topic.